المحتوى النحوي والصرفي في بعض كتب النحو المتداولة بين المتخصصين : دراسة وصفية تحليلية - سالم، عادل علي (Kulliyah of Islamic Revealed Knowledge and Human Sciences,al-Jami'at al-Islamiyyah al- 'Alamiyyah Maliziya, 2020)
The study examines the need for a comprehensive text on grammar for accurate scientific review by looking at grammatical rules and the definitions that are contained in texts on grammar mentioned in this study. The study collected some data on grammatical samples or evidence from different texts on Arabic grammar which are analysed. The analysis will be done through descriptive analytical approach which will include evidence from the Holy Quran and Arabic poetry. The study will also include unconventional grammatical rules which appeared in the Holy Quran and poetry that would compel grammarians, teachers and students to think beyond what had been prescribed by classical grammarians in light of new contexts predicated by the modern world. By doing so, a more accurate applications of grammatical structures can be achieved especially when applied in a more scientific manner.